Educational Pearls Behind The Phase Of Birth And Forty Years Before Prophethood (Reinterpretation Of The Prophetic Head By Sheikh Shafiyyurrahman Al-Mubarakfuri) - Hendrikus Maku (Jurnal Mamangan, 2023)
If in the clouds there is always water that will fall to wet the barren earth, this is also the case with every story in the sirah nabawiyah. The aim of this research is to find educational pearls behind every story or event. There are two methods that will be used in this research, namely: first, using "Library Research" where the method in this research will use theories taken from literature books that support and are relevant to the title of this research. Second, researchers use field research that is appropriate to the object the researcher chooses. This research is a type of field research with a qualitative approach. This research is also supported by library research, namely data sources in the form of books or literature related to the discussion. The results and discussion of this research study are that the "birth and forty years before prophethood" phase of the sirah nabawiyah does not merely contain a series of meaningless stories. In each story or event from this phase, various educational pearls are contained. The conclusion of this study is that readers of the prophet's life history can capture many inspiring moral messages. If so, we can break the expression uthlub al-'ilm walau bi ash-shiin (seek knowledge even in China) with a more Islamic thesis, namely uthlub al-'ilm bi al-qiraat wa al-ta'malu fi sirah nabawiyah .